The Relationship Between Grammar And Reading Comprehension In Tests Of Arabic As A Foreign Language - Islam Youssry Elhadki (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
The aim of this study was to explore the relationship between the performance of learners of Arabic as a foreign language (AFL) in grammar tests and reading comprehension tests. The participants ranged from beginner to upper intermediate levels. We adopted a quantitative approach by analyzing the test results of 394 students over the 2022-2024 academic years. Pearson’s correlation coefficient and linear regression were used to examine relationships between grammar scores and reading comprehension scores. The findings revealed a strong positive correlation between students’ performance in grammar and reading comprehension across all proficiency levels. Moreover, grammar test performance was a strong predictor of performance in reading comprehension, and vice versa. These results highlight the strong interconnection between grammatical competence and reading comprehension among the study sample. The results also align with findings from previous research on other foreign languages. This study represents a novel contribution to the field of teaching AFL.